2007
DOI: 10.1111/j.1742-6723.2007.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine in India: Why are we unable to ‘walk the talk’?

Abstract: The largest democracy on earth, the second most populous country and one of the most progressive countries in the globe, India, has advanced tremendously in most conventional fields of Medicine. However, emergency medicine (EM) is a nascent specialty and is yet to receive an identity. Today, it is mostly practised by inadequately trained clinicians in poorly equipped emergency departments (EDs), with no networking. Multiple factors such as the size of the population, variation in standards of medical education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Such differences have been noted in a range of services, including emergency medicine,[51] obstetrics[52] and paediatric care. [53] Health systems strengthening with development of nationally accepted management protocols for all levels of health care and appropriate monitoring for quality and accessibility are the foundation for improved health care across the board.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences have been noted in a range of services, including emergency medicine,[51] obstetrics[52] and paediatric care. [53] Health systems strengthening with development of nationally accepted management protocols for all levels of health care and appropriate monitoring for quality and accessibility are the foundation for improved health care across the board.…”
Section: Discussionmentioning
confidence: 99%
“…David et al, in their landmark article, suggested that one of the three important prongs essential for the development of emergency medicine in India was the development of formal education in emergency medicine with its recognition as a specialty by the Medical Council of India [22]. …”
Section: Emergency Medicine Educationmentioning
confidence: 99%
“…However, emergency medicine (EM) is a nascent specialty in India, and its development has been protracted and inadequate. [12]…”
Section: Introductionmentioning
confidence: 99%